Histone H1 plays a role in heterochromatin formation and VSG expression site silencing in Trypanosoma brucei. - Megan L Povelones; Eva Gluenz; Marcin Dembek; Keith Gull; Gloria Rudenko (PLoS Pathogens)
The African sleeping sickness parasite Trypanosoma brucei evades the host immune system through antigenic variation of its variant surface glycoprotein (VSG) coat. Although the T. brucei genome contains ∼1500 VSGs, only one VSG is expressed at a time from one of about 15 subtelomeric VSG expression sites (ESs). For antigenic variation to work, not only must the vast VSG repertoire be kept silent in a genome that is mainly constitutively transcribed, but the frequency of VSG switching must be strictly controlled. Recently it has become clear that chromatin plays a key role in silencing inactive ESs, thereby ensuring monoallelic expression of VSG. We investigated the role of the linker histone H1 in chromatin organization and ES regulation in T. brucei. T. brucei histone H1 proteins have a different domain structure to H1 proteins in higher eukaryotes. However, we show that they play a key role in the maintenance of higher order chromatin structure in bloodstream form T. brucei as visualised by electron microscopy. In addition, depletion of histone H1 results in chromatin becoming generally more accessible to endonucleases in bloodstream but not in insect form T. brucei. The effect on chromatin following H1 knock-down in bloodstream form T. brucei is particularly evident at transcriptionally silent ES promoters, leading to 6-8 fold derepression of these promoters. T. brucei histone H1 therefore appears to be important for the maintenance of repressed chromatin in bloodstream form T. brucei. In particular H1 plays a role in downregulating silent ESs, arguing that H1-mediated chromatin functions in antigenic variation in T. brucei.